Características do Conselho de Administração e análise do desempenho em cooperativas de créditos - Gustavo Henrique de Lima (2017)
The Resolution CMN 4.434/2015, Art. 27, caput and §1, established, among other things, that the traditional credit cooperatives that have an average of total assets in the last three fiscal years, equal to or greater than R$50.000.000, and full credit unions must adopt an administrative structure composed of a board of directors an executive board subordinate to it, being prohibited the simultaneous exercise of positions in the board of directors and in the board of directors, and should implement this structure in the first election of directors, carries out from 2017. Therefore, the present study had as a general objective to analyze if, in the Brazilian credit cooperatives, the duality exists between the position of president of the cooperative and president of the board of directors while looking at what is there relation of this governance structure with the financial performance of these cooperatives in 2015. For this investigation, we first carried out an analysis to classify the sample cooperatives as DUAL (president of the cooperative is also chairman of the board of directors) and CMC (cooperative chairman is non-chairman member). The DUAL and CMC variables were separated into two databases. One (DUAL) with 65 cooperatives plus 13 completely independent and another (CMC) with 65 cooperatives plus 13 totally independent, totaling 78 observations in each database, thus allowing comparison. Subsequently, the duality impact on the performance of credit cooperatives was verified, through regression models: Linear cross-sectional type using the Ordinary type using the Ordinary Least Squares (OLS) method. For each dependent variable (ROE Return on Equity, ROA Return on Asset, ROI Return on Investment, CPLA Growth in Shareholders Equity and MB Gross Margin), four models were estimated. Two models, with and without outliers for DUAL independent variables and two models with and without outliers for the CMC variable. Totaling 20 models. Statistical significance was not found in any of the estimated models to assert that the duality of the board of directors positively or negatively affects the performance of Brazilian credit cooperatives in 2015. It is important to understand that duality affects performance before the validity of the aforementioned resolution, helps in the process of elaborating regulatory policies that may have an effect on cooperatives. However, statistical significance was not obtained to support some of the regulatory agencies of credit cooperatives. In any case, this study contributed to the discussion of the gorvenance structure adopted by Brazilian credit cooperatives in the year 2015.